Demandas do movimento ambiental por áreas verdes em Fortaleza - Costa, Ademir da Silva (2011)
It shows an overview of the history of social movements in environmental nature of Fortaleza, state of Ceará, in the period from 1970 to 2011, their demands for the institution, maintenance and / or preservation of green areas of the city, its strategies, difficulties and achievements. It also makes a critical analysis of the growth of Fortaleza, in the light of sustainable development, the concept of the World Commission on Environment and Development, the United Nations. It uses as methods the oral history and the participant observation to address, in a territory that is a urban booming, the dispute between twenty civil society movements and the power concentrated in the retainers of means of production and the state apparatus, under the hegemony of capital.